The relationship of Perak Malay ‘kampung’ elements to the Malaysian Garden Concept (MGC) : Impact on national identity / Ahmad Zamil Zakaria, Hazreena Hussein and Melasutra Md Dali - Zakaria, Ahmad Zamil; Hussein, Hazreena; Md Dali, Melasutra (Universiti Teknologi MARA, Perak, 2021)
'Kampung' is a place that is very closely related to the Malay community in Malaysia. It is a place the Malays adapt to their real life. The elements of landscape and garden that intend to be highlighted are found to be unatrractive to designers. The image and identity of features are no longer a priority for the homeowners to inherit. The objective of this study is to identify the garden elements that abide by the Malaysian Garden Concept's (MGC) basic guidelines in the environment of traditional Perak 'kampung' houses. . This study emphasizes qualitative methods that lead to site observations and interviews. The study was conducted on 71 traditional houses in Perak. The findings indicate that most of the 'kampung' landscape elements do not significantly impact supporting guidelines by the National Landscape Department (NLD).